The crystallography of metal halides formed within single walled carbon nanotubes - Sloan, J; Brown, G; Bailey, SR; Coleman, K; Flahaut, E; Friedrichs, S; Xu, C; Green, M; Dunin-Borkowski, R; Hutchison, J; Kirkland, A; Meyer, R (2001)
The crystal growth behaviour and crystallography of a variety of metal halides incorporated within single walled carbon nanotubes (SWNTs) as determined by high resolution electron microscopy (HRTEM) is described. Simple packed structures, such as the alkali halides, form related structures within SWNTs that are found to be integral atomic layers in terms of their thickness as a function of the encapsulating SWNT diameter. An enhanced HRTEM image restoration technique reveals precise data concerning lattice distortions present in these crystals. More complex structures, such as those derived from 3D complex, layered and chain halides form related crystal structures within SWNTs. In narrow SWNTs (i.e. with diameters less than ca. 1.6 nm), structures consisting of individual 1D polyhedral chains (1D-PHCs) were obtained that were derived from the corresponding bulk halides structures. In the case of infinite 3D network and layered halides, the 1D polyhedral chains form with lower co-ordinations than in the bulk. Molecular halides also intercalate into SWNTs but these do not readily form organised structures within SWNTs.